Factor Xa and thrombin induce endothelial progenitor cell activation. The effect of direct oral anticoagulants. (18th August 2021) - Papadaki, Styliani; Sidiropoulou, Sofia; Moschonas, Iraklis C.; Tselepis, Alexandros D.
Abstract: Factor Xa (FXa) and thrombin exert non-hemostatic cellular actions primarily mediated through protease-activated receptors (PARs). We investigated the effect of FXa and thrombin on human late-outgrowth endothelial cells (OECs), a type of endothelial progenitor cells (EPCs), and on human umbilical vein endothelial cells (HUVECs). The effect of direct oral anticoagulants (DOACs), rivaroxaban and dabigatran, was also studied. The membrane expression of intercellular adhesion molecule-1 (ICAM-1) and the secretion of monocyte chemoattractant protein-1 (MCP-1) were used as cell activation markers. FXa and thrombin increase the ICAM-1 expression and the MCP-1 secretion on both cells, being higher on OECs. Vorapaxar, a specific PAR-1 antagonist, completely inhibits FXa-induced activation of both cells and thrombin-induced HUVEC activation, but only partially thrombin-induced OEC activation. Furthermore, thrombin-receptor activating peptide; TRAP-6, only partially activates OECs. OECs do not membrane-express PAR-4, therefore it may not be involved on thrombin-induced OEC activation. Rivaroxaban and dabigatran inhibit OEC and HUVEC activation by FXa and thrombin, respectively. Rivaroxaban enhances thrombin-induced OEC and HUVEC activation, which is completely inhibited by vorapaxar. The inhibition of OEC and HUVEC activation by vorapaxar and DOACs may represent a new pleiotropic effect of these drugs. The pathophysiological and clinical significance of our findings need to be established.